PERSPECTIVE—Explaining Influence Rents: The Case for an Institutions-Based View of Strategy - Ahuja, Gautam; Yayavaram, Sai (Organization Science, 2011)
Research in strategy has identified and tried to explain four types of rents: monopolistic rents, efficiency rents, quasi rents, and Schumpeterian rents. Building on previous work on political and institutional strategies, we add a fifth type of rent: influence rents. Influence rents are the extra profits earned by a firm because the rules of the game (laws, regulations, and informal rules) are designed or changed to suit it. To aid the analysis of the relationship between institutional context and firm performance and to provide a structure to guide research, we develop a framework with five key components: (a) an identification of the five fundamental problems of a market economy, (b) a typology that describes the five different types of institutions that emerge to solve these problems, (c) the market-ordering mechanisms used by institutions to solve these problems, (d) the common causes of weak institutional performance, and (e) generic strategies used by firms to exploit these weaknesses of an institutional context to enhance firm performance. We highlight potential applications of the framework as well as an illustrative research agenda that can advance the development of theory to explain the emergence and persistence of influence rents.